RESOURCE ALLOCATION AND JOB SCHEDULING POLICY IN DESKTOP GRID COMPUTING - PEYVANDI, SOODEH (2015)
Many scientific and engineering projects such as SETI @ home and Distributed.net are consuming resources of distributed internet-connected idle computers, known as 'volunteers, for executing or computing their jobs. This type of large distributed system is referred to as desktop grid (DG) computing system or \ volunteer computing (VC) system In the desktop grid computing environment a huge scientific project will be broken down into small independent units or tasks and passed to some available idle volunteers for parallel execution. However, these volunteers have one major issue. which is volatility. In other words. their availability throughout job execution cannot be guaranteed and rs up to the jurisdiction of the owners. Hence, resource allocation and JOb scheduling are two main components which are very critical for a desktop grid system. Both have rmportant roles 111 ensuring eftkienL effective and successful execution of jobs.